Cerebrospinal fluid biomarkers provide evidence for kidney-brain axis involvement in cerebral malaria pathogenesis - Conroy, Andrea L.; Datta, Dibyadyuti; Opoka, Robert O.; Batte, Anthony; Bangirana, Paul; Gopinadhan, Adnan; Mellencamp, Kagan A.; Akcan-Arikan, Ayse; Idro, Richard; John, Chandy C. (Frontiers in Human Neuroscience, 2023)
Introduction Cerebral malaria is one of the most severe manifestations of malaria and is a leading cause of acquired neurodisability in African children. Recent studies suggest acute kidney injury (AKI) is a risk factor for brain injury in cerebral malaria. The present study evaluates potential mechanisms of brain injury in cerebral malaria by evaluating changes in cerebrospinal fluid measures of brain injury with respect to severe malaria complications. Specifically, we attempt to delineate mechanisms of injury focusing on blood-brain-barrier integrity and acute metabolic changes that may underlie kidney-brain crosstalk in severe malaria. Methods We evaluated 30 cerebrospinal fluid (CSF) markers of inflammation, oxidative stress, and brain injury in 168 Ugandan children aged 18 months to 12 years hospitalized with cerebral malaria. Eligible children were infected with Plasmodium falciparum and had unexplained coma. Acute kidney injury (AKI) on admission was defined using the Kidney Disease: Improving Global Outcomes criteria. We further evaluated blood-brain-barrier integrity and malaria retinopathy, and electrolyte and metabolic complications in serum. Results The mean age of children was 3.8 years (SD, 1.9) and 40.5% were female. The prevalence of AKI was 46.3% and multi-organ dysfunction was common with 76.2% of children having at least one organ system affected in addition to coma. AKI and elevated blood urea nitrogen, but not other measures of disease severity (severe coma, seizures, jaundice, acidosis), were associated with increases in CSF markers of impaired blood-brain-barrier function, neuronal injury (neuron-specific enolase, tau), excitatory neurotransmission (kynurenine), as well as altered nitric oxide bioavailability and oxidative stress (p < 0.05 after adjustment for multiple testing). Further evaluation of potential mechanisms suggested that AKI may mediate or be associated with CSF changes through blood-brain-barrier disruption (p = 0.0014), ischemic injury seen by indirect ophthalmoscopy (p < 0.05), altered osmolality (p = 0.0006) and through alterations in the amino acids transported into the brain. Conclusion In children with cerebral malaria, there is evidence of kidney-brain injury with multiple potential pathways identified. These changes were specific to the kidney and not observed in the context of other clinical complications.